Assessment of the Financing Framework for Municipal Infrastructure in Vietnam - World Bank (Washington, DC, 2014)
A fundamental challenge for Vietnam is to improve the affordability and efficiency of infrastructure investment. The fragmentation of public infrastructure investment results in duplication and waste, and is a major underlying cause of investment inefficiency. Bond issuance has been the most prominent form of debt financing at the sub-national level. At the provincial level, significant disconnects exist between total planned investment needs in infrastructure, and the effective demand for such investment. The success of any initiative to improve the financing of municipal infrastructure in Vietnam hinges on advances in the broader landscape of policy reform as part of the country's long-term development. Meeting these challenges requires a comprehensive approach that addresses issues of governance, financing, and execution. This report has been formulated with the objective of informing the Government of Vietnam (GOV) on how the financing framework for municipal infrastructure in the country can be strengthened. It is based on an assessment of the constraints and opportunities that sub-national governments face in accessing financing for infrastructure development. It also draws upon lessons and good practices from international experience in this area, considering their relevance for Vietnam. A set of recommendations and implementable actions is provided, recognizing the broader context of ongoing reforms that are needed on institutions, incentives and the availability of information.